Study of Assessment of the complications for Patients Associated with Transurethral resection of benign prostate Hyperplasia (Turp) (Journal of the College of Basic Education, 2022)
Objective: To assess the complications for patients associated with TURP, and Identify the relationship between the complications with some demographic variable , post operative data , and past history of the patient with TURP.Methodology: A descriptive study was conducted on (78) patients with TURP, who were admitted in the urological floor and out patient urological clinics, was selected out of four Teaching Hospitals in Baghdad city The study was carried out during the period of 1st of June 2007 to the 1st of November 2008. The questionnaire consisted of (2) a major part, The first part is concerned with socio-demographic characteristics of these patients. The second part is concerned with post operative data and complications characteristics of these patients. Data were collected through the use of the questionnaire; the data collection was carried out during the period of 7th of October 2007 to the 30th of May 2008. Data were analyzed through the application of the descriptive and the inferential statistical data analysis approach.Result: The findings of the study proved that, the socio – demographic characteristics of the TURP patients were (age, occupation status, education level, residential area, alcohol drinking, and smoking, had a significant difference effect . also the findings of the study proved that, the post operative data(duration of catheter , duration of irrigation , irrigation volume, and hospital stay duration), and past history of the patient had a significant difference effect for the complications post TURP.